Digital Democracy Is Coming to the Maine Legislature - Carleton, Joseph (Maine Policy Review, 1998)
Although Maine’s information infrastructure is several years ahead of the nation in development, Maine ranks only 41st out of 50 states in its "Digital Democracy," that is, its use of new telecommunications and information technologies to permit greater citizen access to laws, legislators and the state’s legislative processes. State Rep. Joseph Carleton outlines changes underway in the Maine Legislature that will result in greater digital democracy throughout the state. Through advances such as e-mail, the Internet, and other digital forms of communication, Carleton envisions new ways of doing business both for legislators and citizens. In discussing the effects of such changes, he poses some tough questions: Will e-mail improve the efficiency of communications between legislators and constituents, or will it become an outlet for mass advocacy campaigns that unnecessarily burden legislators with hundreds of messages daily? Will electronic discussion sites improve consensus building, or will they strengthen the ability of fringe groups to temporarily coalesce and, therefore, block the wishes of the majority? Will the Internet improve legislators’ access to independent and objective information, or will it not? Carleton concludes by noting that digital democracy not only will change how legislators do their work, but has broader implications for democracy as well.